Statistical Approach of the Role of the Conserved CSB-PiggyBac Transposase Fusion Protein (CSB-PGBD3) in Genotype-Phenotype Correlation in Cockayne Syndrome Type B - Damaj-Fourcade, Rayanne; Meyer, Nicolas; Obringer, Cathy; Le May, Nicolas; Calmels, Nadège; Laugel, Vincent (Frontiers in Genetics, 2022)
Cockayne syndrome is a rare condition that encompasses a very wide spectrum of clinical severity. Mutations upstream of a transposon called PiggyBac Transposable Element Derived 3 in intron 5 of the CSB/ERCC6 gene could bring about less severe forms than mutations located downstream of that transposon insertion. Our aim was to study genotype-phenotype correlation by determining whether the position of each mutation of the CSB/ERCC6 gene has an impact on the phenotype. A hundred and forty-seven Cockayne patients, who had two pathogenic mutations in the CSB/ERCC6 gene and for whom clinical data was available, were retrospectively selected and included in the study. Data analysis was performed under the Bayesian paradigm. Analysis of the proportion of the different subtypes of Cockayne syndrome according to the position of the mutations was done using an ordinal logistic regression model. Using a vague prior, the risk of developing a more severe subtype when exposed to 2 mutations downstream compared to 2 mutations upstream was 2.0 [0.9 – 4.5]. Estimations varied through the sensitivity analysis. We could reasonably conclude that a relationship between the number of downstream mutations and the Cockayne syndrome clinical expression exists but it is still difficult to give a precise estimate of this relationship. The real effect could be more complex that the one described in the initial model and other genetic factors might be taken into consideration together with the mutation site to better explain clinical variability.